Thrombosis in cancer patients: etiology, incidence, and management - Sheth, Rahul A.; Niekamp, Andrew; Quencer, Keith B.; Shamoun, Fadi; Knuttinen, Martha-Gracia; Naidu, Sailendra; Oklu, Rahmi (Cardiovascular Diagnosis and Therapy, 2017)
Venous thromboembolism (VTE) is the second most common cause of mortality in cancer patients. The mechanisms of cancer-associated thrombosis (CAT), much like cancer itself, are multi-factorial and incompletely understood. Cancer type, stage, tumor-derived factors and genetics all affect CAT risk. Furthermore, cancer therapies as well as the indwelling vascular devices through which these therapies are delivered can increase the risk for CAT. In this review, we summarize mechanisms of hypercoagulability in cancer patients, patterns of thrombosis associated with cancer, current guidelines for the diagnosis and management of CAT, and important considerations regarding the placement of implantable vascular devices in the care of cancer patients with VTE.